The native speaker programme: a qualitative study on novice ESL teachers’ knowledge, identity and practice / Fatiha Senom - Fatiha , Senom (2016)
Drawing on a recent construct by Kiely and Askham (2012), Furnished Imagination, this study explores the influences of a newly implemented mentoring programme, the “Native Speaker Programme” on four novice ESL teachers’ learning experience in their first year of teaching. The purpose of this study was to provide a comprehensive understanding on novice teacher learning through the examination of the influences of the programme on the novice teachers’ professional knowledge, professional practice, and professional identity. Employing a multiple case study, the data collection techniques of this qualitative study included in-depth interview, observations, and document analysis. The data were analysed manually to get the feel of the data and described in order to explore the influences of the “Native Speaker Programme” on the novice teachers’ learning experience, particularly on their professional knowledge, practice and identity. The study found that the programme contributed to novice ESL teachers’ professional knowledge by bridging the gap between their pre-service training and real classroom, expanding their knowledge-base, and providing effective conditions of mentoring. The data implied that positive qualities of mentors, constructive roles of mentors, and effective mentoring strategies as important conditions for effective mentoring. Additionally, the study discovered that the programme influenced novice ESL teachers’ professional practice particularly on their classroom management, ways of motivating students, teaching methodology, selection of teaching materials, and engagement in reflective practice. Furthermore, the study suggested that the programme changed novice ESL teachers’ professional identity by inculcating them with positive values, empowering their self-confidence, promoting positive perception on teaching profession, and inspiring them to embrace their identity as nonnative ESL teachers. Moreover, the findings of the study indicated an inextricable interrelationship between novice ESL teachers’ professional knowledge, practice, and identity. This study concluded that teachers’ professional knowledge, practice, and identity are mutually forming, informing, reforming, and transforming. Based on the findings, the study discussed the implication of the study to the body of knowledge, Second Language Teacher Education (SLTE) pedagogy and practice, and future research. The study also holds a significant theoretical implication for second language teacher learning as it contributes to the establishment of Kiely and Askham’s (2012) construct of Furnished Imagination as an effective and constructive conceptual framework that allows for in-depth insight in understanding novice teacher learning in an early training context.